2007
DOI: 10.1364/ol.32.000772
|View full text |Cite
|
Sign up to set email alerts
|

Multiwall carbon nanotube absorber on a thin-film lithium niobate pyroelectric detector

Abstract: Multiwall carbon nanotubes (MWNTs) were applied in a bulk layer to a pyroelectric film to increase the detector sensitivity nearly fourfold without a substantial penalty to the low-frequency response (4-100 Hz). In addition, the spectral sensitivity over the wavelength range from 600 to 1800 nm was uniformly enhanced, with variations less than 1%. The results demonstrate the suitability of MWNTs as an efficient thermal absorber having low thermal mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…This is well within the uncertainty of the previous study [8] hence the results of the two studies are in agreement. Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This is well within the uncertainty of the previous study [8] hence the results of the two studies are in agreement. Fig.…”
Section: Resultssupporting
confidence: 91%
“…A previous evaluation [8] showed that the spectral responsivity of this detector was flat in the 600 nm-1.8 lm wavelength range.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Carbon nanotubes were successfully applied in the past onto pyroelectric LiNbO 3 crystals and films [4] to improve the performance of infrared detectors. However, such devices require large pieces of thermoelectric coatings to work and they lack the flexibility of buckypaper.…”
mentioning
confidence: 99%